Development of a highly efficient oil degumming process using a novel phosphatidylinositol-specific phospholipase C enzyme - Cerminati, Sebastián (2017)
Enzymatic degumming using phospholipase C (PLC) enzymes may be used in environmentally friendly processes with improved oil recovery yields. In this work, phosphatidylinositol-specific phospholipase C (PIPLC) candidates obtained from an in silico analysis were evaluated for oil degumming. A PIPLC from Lysinibacillus sphaericus was shown to efficiently remove phosphatidylinositol from crude oil, and when combined with a second phosphatidylcholine and phosphatidylethanolamine-specific phospholipase C, the three major phospholipids were completely hydrolyzed, providing an extra yield of oil greater than 2.1%, compared to standard methods. A remarkably efficient fed-batch Escherichia coli fermentation process producing ∼14 g/L of the recombinant PIPLC enzyme was developed, which may facilitate the adoption of this cost-effective oil-refining process.